The Influence of Cashless Transaction Usage on Generation Z's Consumptive Behavior Moderated by Hedonic Lifestyle - Muhammad Adib Mawardi; Bambang Septiawan; Nabella Vatkumia Safitri (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
This study aims to examine the influence of cashless transaction usage on Generation Z’s consumptive behavior and to determine whether hedonic lifestyle moderates the relationship. The research was conducted using a quantitative cross-sectional approach. Data were collected from 123 Generation Z respondents in Blitar City and its surrounding areas through a structured questionnaire. The questionnaire measured cashless transaction usage, consumptive behavior, and hedonic lifestyle. Data were analyzed using IBM SPSS Statistics and Hayes’ PROCESS macro (Model 1) for moderation analysis. The results showed that the overall model was statistically significant and explained 56.4% of the variance in consumptive behavior. However, cashless transaction usage did not have a significant direct effect on consumptive behavior. Hedonic lifestyle also did not significantly moderate the relationship. Instead, hedonic lifestyle had a strong direct positive effect on consumptive behavior. These findings indicate that hedonic lifestyle, rather than cashless payment habits, is the main driver of impulsive and excessive consumption among Generation Z in this regional setting. The study contributes to consumer behavior theory by showing the important role of lifestyle factors in a cashless economy. Practically, the results can help fintech companies, educators, and policymakers create better programs to promote responsible spending among young people.